Development of An Integrated Biodiversity Biology Module With Local Potential of Andaliman Plants (Zanthoxylum acanthopodium) at Senior High School - Harahap, Dina Liani; Tanjung, Indayana Febriani; Reflina, Reflina (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
Biology teachers have not made regional potential a source of learning. The natural environment around the school is used to support teacher explanations that do not create exploratory. This study aims to determine the validity, practicality, and effectiveness of the integrated module of the local potential of South Tapanuli for the biodiversity of the Andaliman (Zanthoxylum acanthopodium DC) plant. The research uses the Research and Development (R&D) method referring to the 4-D development model developed by Thiagarajan. The small group trial subjects consisted of 14 students of class X MIA-1. The results of the development module research show validity values of 87% and 95% by teaching module and material experts, 87% and 83% practicality values by biology teachers and students, while effectiveness based on individual mastery of student learning outcomes achieves classical mastery of 85% . The overall results meet the valid, practical and effective categories, so that the development module deserves to be a teaching material in learning activities about andaliman plants.ABSTRAK: Guru biologi belum menjadikan potensi daerah sebagai sumber belajar. Lingkungan alam sekitar sekolah dimanfaatkan sebatas mendukung penjelasan guru yang tidak menciptakan eksploratif. Penelitian bertujuan mengetahui kevalidan, kepraktisan, dan keefektifan modul terintegrasi potensi lokal Tapanuli Selatan keanekaragaman hayati tumbuhan andaliman (Zanthoxylum acanthopodium DC). Penelitian menggunakan metode Research and Development (R&D) mengacu model pengembangan 4-D dikembangkan Thiagarajan. Subjek uji coba kelompok kecil terdiri 14 peserta didik kelas X MIA-1. Hasil penelitian modul pengembangan menunjukkan nilai kevalidan 87% dan 95% oleh ahli modul ajar dan materi, nilai kepraktisan 87% dan 83% oleh guru biologi dan peserta didik, sementara keefektifan berdasarkan ketuntasan individual dari hasil belajar peserta didik mencapai ketuntasan secara klasikal sebesar 85%. Keseluruhan hasil memenuhi kategori valid, praktis dan efektif, sehingga modul pengembangan layak menjadi bahan ajar didalam kegiatan pembelajaran mengenai keragaman tumbuhan andaliman.